Sociology of Extremism - Jipson, Art (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Course DescriptionThis may be one of the most important classes that you take at this university. This course will provide an overview of terrorism and political extremism in the United States, with a focus on domestic white racialist and anti-government organizations. The sociological purpose of this course is to acquaint you with the social understanding and nature of identity, otherness, difference, and social construction of the enemy from the perspective of the historic development of white racial extremism. This course is designed to acquaint students with some of the literature of social movements, stratification, organizations, and race and ethnicity that assist in the understanding of enemy construction. Movements, groups, and individuals that use a conceptualization of enemies as rhetoric, mobilization strategy, and organization tools will also be a consistent theme of the course. The review of ideas will include classical and contemporary ideas, sociological concepts, frameworks, and theories. If students desire a seminar purely on policy, policing or criminal justice practice, they are advised to seek a different course. This course will utilize a variety of student-generated learning styles, collaborative models, and electronic learning to examine the course materials.